MEK inhibitors activate Wnt signalling and induce stem cell plasticity in colorectal cancer - Tianzuo Zhan (Nature Portfolio, 2019)
Wnt signaling is necessary for colorectal cancer tumorigenesis and stem cell maintenance. Here, the authors identify MEK1/2 inhibitors as potent activators of Wnt/β-catenin signalling and show that clinically approved MEK inhibitors inadvertently induce stem cell plasticity in colorectal cancer